Mikiso Hane. (comp. y trad.). Reflections on the Way to the Gallows. Rebel Women in Prewar Japan. Berkeley, CA: University of California Press, 1988. - Tanaka, Michiko; Hane, Mikiso (Estudios de Asia y África, 1996)
-